Meningkatkan Prestasi Belajar Dengan Lingkungan Sebagai Media Pembelajaran - Muharrina Muharrina (JURNAL GLOBAL EDUKASI, 2022)
Abstract: Classroom action research in general aims to improve the quality of learning for fourth grade students at SDN 010047 Sei Alim Ulu. Specifically, it aims to: (1) Improve Learning Achievement with the Environment as a Learning Media for Circular and Extensive Materials in Mathematics Lessons for Fourth Grade Students at SDN 010047 Sei Alim Ulu district Air Joman academic year 2019/2020; (2). Describe the management of Mathematics learning. This classroom action research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing and reflecting. Classroom action research was carried out in the fourth grade of SDN 010047 Sei Alim Ulu with a total of 35 students. The subjects of this study were fourth grade mathematics teachers and fourth grade students at SDN 010047 Sei Alim Ulu. The data were collected through observation, interviews, tests, and study documentation. Keywords: environment; instructional Media; two-dimentional figure Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas IV SDN 010047 Sei Alim Ulu. secara khusus bertujuan untuk: (1) Meningkatkan hasil belajar dengan Lingkungan Sebagai Media Pembelajaran Materi Keliling dan Luas Pada Pelajaran Matematika Siswa Kelas IV SDN 010047 Sei Alim Ulu kec. Air Batu TP. 2019/2020; (2) Mendeskripsikan pengelolaan pembelajaran Matematika. Penelitian tindakan kelas ini dilaksanakan dalam dua siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas dilaksanakan dikelas IV SDN 010047 Sei Alim Ulu yang berjumlah 35 orang siswa. Subjek penelitian ini adalah guru Matematika kelas IV dan siswa kelas IV SDN 010047 Sei Alim Ulu, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata Kunci: lingkungan; media pembelajaran; bangun datar